Historical Review of Non-suspension Rule with an Approach to Mohaghegh Yazdi’s Opinions Criticizing the Famous Viewpoint - ?????? ??????, ??? ??? ????; ??????, ???????; ?????, ???? ??? (???????? ??????? ?????? ????)
According to the Shiite jurisprudence literature, non-suspension of contracts and unilateral legal acts is among the general rules of contracts jurisprudence and has been criticized by Shiite jurists in the last two centuries. The following are the main issues dealt with in this paper: historical background of non-suspension rule, its formation over time and its conversion into a general rule, introduction of the Shiite jurists who have contributed to this conversion, identification of the fields and trends of criticizing this rule, and given Sahib Orvah's special place in the criticism field and in offering particular jurisprudence opinions, discovering his role in criticizing the famous opinion and promoting a new one. The purpose of this paper is to clarify the above said issues through a historical and with a person-centered approach in order to introduce a part of Shiite jurisprudence history in the general rules of contracts jurisprudence area. Therefore, the present paper begins with subjectology of non-suspension rule in the Shiite jurisprudence literature from Mohaghegh Yazdi?s viewpoint and after trying to find out the background of this rule in the Shiite jurisprudence, explains Sahib Orvah?s opinion, its bases and his critique of the famous opinion.